The iSquare protocol: combining research, art, and pedagogy through the draw-and-write technique. (August 2018) - Hartel, Jenna; Noone, Rebecca; Oh, Christie; Power, Stephanie; Danzanov, Pavel; Kelly, Bridgette
This article introduces the iSquare protocol, a novel application of the draw-and-write technique. The protocol was developed in the field of information science to explore the visual dimension of information and as an alternative and complement to written definitions of information that dominate the literature. In addition to generating a new visual perspective on information, the approach has proven fruitful for artistic and pedagogical purposes. Here, the protocol is presented in detail for scholars within information science and those beyond who may adapt it to their own research questions. The article begins with an overview of the draw-and-write technique, followed by a history of its use in the iSquare Research Program. Then, the distinguishing features of the iSquare protocol, its artistic potentials and teaching applications are outlined. Links are provided to an instructional script and research instrument template, enabling turnkey implementation of the method.